An Ecore Metamodel for the W3C PROV Provenance Data Model - Vieira, Marcos Alves; Velasco, Gislainy Crisostomo; Carvalho, Sergio T. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: In contemporary Information Systems development, effective management of data provenance has become pivotal for ensuring transparency, accountability, and reproducibility, particularly in the context of data-intensive applications. Problem: Despite the emergence of the W3C PROV family of documents as a standard for representing provenance, challenges persist in seamlessly integrating provenance information into Information Systems software development processes. Solution: This paper introduces the Ecore4PROV-DM metamodel, meticulously designed to adhere to the specifications of the W3C PROV data model (PROV-DM). IS Theory: We employed the Representation Theory to create an Ecore metamodel for representing the W3C PROV data model. Method: Model-Driven Engineering techniques were applied to create an Ecore metamodel that faithfully represents the PROV-DM concepts. Utilizing the Metamodel Quality Requirements and Evaluation (MQuaRE) framework, we conducted a meticulous assessment of Ecore4PROV-DM, ensuring its fidelity in representing PROV-DM concepts, evaluating completeness, correctness, and usability. Results: The metamodel quality evaluation results demonstrate a high consensus among metamodeling experts on the accuracy and completeness of Ecore4PROV-DM in capturing PROV-DM nuances. While specific concerns were raised about certain concepts, the overall assessment underscores Ecore4PROV-DM as a robust and reliable metamodel for modeling provenance information. Contributions and Impact in IS: This work contributes by delivering a well-defined and thoroughly evaluated Ecore metamodel for PROV-DM, providing a foundation for developing Information Systems that require precise provenance representation. The systematic structure of the metamodel enhances its utility and reliability. This metamodel provides a systematic and formalized approach to represent and manage provenance information, addressing the gap between the conceptual richness of W3C PROV-DM and the practical needs of Information Systems developers.